2002
DOI: 10.1161/01.hyp.0000018590.26853.c7
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Reduces Central and Peripheral Sympathetic Nerve Activity in a Rat Model of Neurogenic Hypertension

Abstract: Abstract-We have developed a new model of neurogenic hypertension in the rat, in which hypertension is caused by injecting 50 L of 10% phenol in the lower pole of one kidney. Administration of phenol in the kidney causes an immediate and persistent rise in blood pressure (BP), norepinephrine (NE) secretion from the posterior hypothalamic nuclei (PH), and renal sympathetic nerve activity (RSNA). Because angiotensin II (Ang II) is known to stimulate central and peripheral sympathetic nervous system (SNS) activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 38 publications
4
57
0
Order By: Relevance
“…This supports our previous observations in rats submitted to isolation or cold-restraint stress and pretreated with candesartan administered subcutaneously (Armando et al 2001;Bregonzio et al 2003). These results are in agreement with recent findings of reduction in central and peripheral sympathetic nerve activity in neurogenic hypertensive rats by the AT 1 receptor antagonist losartan (Ye et al 2002). …”
Section: Effects Of Candesartan Treatment and Cold-restraint Stress Osupporting
confidence: 93%
“…This supports our previous observations in rats submitted to isolation or cold-restraint stress and pretreated with candesartan administered subcutaneously (Armando et al 2001;Bregonzio et al 2003). These results are in agreement with recent findings of reduction in central and peripheral sympathetic nerve activity in neurogenic hypertensive rats by the AT 1 receptor antagonist losartan (Ye et al 2002). …”
Section: Effects Of Candesartan Treatment and Cold-restraint Stress Osupporting
confidence: 93%
“…Several reports, however, showed that AT1-receptor blockers act within the brain, as well as in the peripheral vasculature. [5][6][7][8][9][10]43,44 Different AT1 blockers may thus act centrally or peripherally and block different AT1 receptors. 8,44 Lipophilicity and pharmacokinetics are important factors for determining blood-brain barrier permeability.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that ANG II in the brain plays an important role in maintaining a high level of sympathetic activity in a number of models of experimental hypertension (20,24,44,45). In particular, as mentioned above, very recent studies indicate that, at least in SHR and in the Dahl salt-sensitive hypertensive rat, endogenous ANG II has a tonic excitatory action on presympathetic neurons in the RVLM that is not evident in normotensive animals (1,21,22).…”
Section: Perspectivesmentioning
confidence: 98%